2023
DOI: 10.1111/ijfs.16636
|View full text |Cite
|
Sign up to set email alerts
|

Combinedly increased viability of Lactiplantibacillus plantarum grx16 by co‐encapsulation of cryoprotectants and porous starch within calcium alginate capsules

Tong Zhou,
Wenli Kang,
Yifeng Han
et al.

Abstract: SummaryAlginate‐based encapsulation is an effective probiotics delivery system in the intestine. However, due to calcium ions and gastric juice damaging to cell wall/membrane integrity during freeze‐drying and gastrointestinal ingestion, lots of cell loss their viability. This study, taking Lactiplantibacillus plantarum grx16 as an example, indicated that co‐encapsulation of cryoprotectants and porous starch within calcium alginate capsules could combinedly improve viability of probiotics encapsulated. Compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Co-encapsulation of cryoprotectants and porous starch within calcium alginate capsules (CAC) with Lactiplantibacillus plantarum grx16 showed that the viability of probiotics encapsulated could be improved to 82.68%, as reported by Zhou et al [130].…”
Section: Co-encapsulation Of Multiple Probioticsmentioning
confidence: 67%
“…Co-encapsulation of cryoprotectants and porous starch within calcium alginate capsules (CAC) with Lactiplantibacillus plantarum grx16 showed that the viability of probiotics encapsulated could be improved to 82.68%, as reported by Zhou et al [130].…”
Section: Co-encapsulation Of Multiple Probioticsmentioning
confidence: 67%